Overview of the 3rd isirv‐Antiviral Group Conference – advances in clinical management. Issue 1 (15th November 2014) - Hurt, Aeron C.; Hui, David S.; Hay, Alan; Hayden, Frederick G.
<x xml:space="preserve">Abstract</x> This review highlights the main points which emerged from the presentations and discussions at the 3rd isirv‐Antiviral Group Conference ‐ advances in clinical management. The conference covered emerging and potentially pandemic influenza viruses and discussed novel/pre‐licensure therapeutics and currently approved antivirals and vaccines for the control of influenza. Current data on approved and novel treatments for non‐influenza respiratory viruses such as MERS‐CoV, respiratory syncytial virus (RSV) and rhinoviruses and the challenges of treating immunocompromised patients with respiratory infections was highlighted.